Management Strategy Finance: Analysis Comprehensive Investment Decision Making In Indonesia's Emerging Markets - Abdul Rosid; Agung Budilaksono; Rano Karno; Hartoto, Hartoto; Nasfi, Nasfi; Meity. L. H. Lado (Jurnal Ekonomi, 2024)
The Indonesian financial market has attracted the attention of both local and international investors in the last few decades. With steady economic growth and a variety of investment opportunities available, investment decision making has become critical to achieving long-term financial goals. In this context, comprehensive financial management strategies play a major role in guiding investors through dynamic and complex emerging markets. This article aims to provide a comprehensive analysis of investment decision making in Indonesia's emerging markets, by highlighting several key factors that need to be considered in making effective investment decisions. A qualitative approach was used in this research to gain an in-depth understanding of effective financial management strategies in the context of the developing Indonesian market. Primary data was collected through interviews with financial experts and experienced investors, while secondary data was obtained from related literature, market reports and financial data. The research results show that a comprehensive analysis of investment decision making involves an in-depth evaluation of various factors that influence investment. This includes fundamental and technical analysis, effective risk management, as well as understanding local markets. By applying a comprehensive and detailed approach, investors can reduce risks and increase their chances of achieving profitable returns in Indonesia's emerging markets. In conclusion, a comprehensive financial management strategy is very important in facing the growing dynamics of the investment market in Indonesia. Through a combination of in-depth analysis and effective risk management, investors can maximize the potential returns on their investments and achieve long-term financial goals.